The Waste Management System in the Parking and Traders Arrangement in the Borobudur Temple Area, Central Java, Indonesia - S. Isworo, E. Jasmiene and P. S. Oetari (Nature Environment and Pollution Technology)
The Indonesian government continues to accelerate the resolution of all problems related to the planning, infrastructure development, and arrangement of tourist visits, including the arrangement of parking spaces and commercial areas in the Borobudur temple area. The purpose of this study is to develop a waste management system in the parking and commercial areas of Kujon as an alternative to structuring the Borobudur temple area. The research method is a descriptive-qualitative observational approach. Surface water and groundwater examinations are carried out in laboratories and compared with quality criteria determined by the Indonesian government. Toxic and hazardous waste is stored in temporary facilities until it is collected by a company licensed by the Indonesian environmental ministry. The Shannon-Wiener Plankton and Benthos Diversity Index measures the diversity of organisms in a community. The study’s findings highlight the need to establish a waste processing facility based on the reduction, reuse, and recycling principles. Waste will be collected at a certain site and stored temporarily in line with the technical instructions for the Minister of Environment and Forestry’s Regulation. The findings of surface water and groundwater studies demonstrate that all measured parameters continue to meet the Indonesian government’s quality thresholds. Plankton Bioindicator Measurements: Plankton diversity index values range from 1.040 to 1.943, indicating moderate pollution, while benthos values range from 0.811 to 0.918, indicating weakly to moderately contaminated conditions. Sustainable environmental management is critical and should serve as a baseline for environmental quality in the activity area.